Coronary Au@Bi Nanospheres for Highly Impedance‐Sensitive Immunosensing toward CEA - Caihong Wang; Ruizhuo Ouyang; Jinyao Liu; Yuefeng Zhao; Yuhao Li; Ning Guo; Baolin Liu; Yuqing Miao (Advanced Sensor Research, 2023)
Abstract Novel coronary Au@Bi nanospheres (NSs) are simply synthesized by sparkling gold nanoparticles (Au NPs) on the surface of bismuth (Bi) NSs and successfully used as highly impedance‐sensitive immunosensing platform to develop a new label‐free electrochemical immunosensor for the detection of carcinoembryonic antigen (CEA). Firstly, Bi NSs are prepared by one‐pot hydrothermal method, showing uniform sphere morphology with a dense oxide film formed outside Bi NSs due to the easy oxidation of Bi in the air. The oxide film significantly hinders the transmission of electrons and effectively improves the sensitivity of the proposed electrochemical impedance immunosensor. The surface functionalization of Bi NSs with Au NPs enhances the biocompatibility, stability, as well as active surface area of the produced Au@Bi NSs, preferable for the efficient loading of antibody molecules. The electrochemical impedance spectroscopy (EIS) is selected as the optical technique to measure CEA with the constructed immunosensor based on Au@Bi NSs. Because of the excellent impedance‐responsive performance, this new immunosensor displays highly sensitive detection toward CEA in a linear range of 50 fg mL−1–100 ng mL−1 with an extremely low detection limit of 9.83 fg mL−1 and could be potentially used in early clinical detection of cancer.